2019
DOI: 10.3389/fnins.2019.01258
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Activity-Based Detection Uncovers the Different Release Mechanisms of Seed-Competent Tau Versus Inert Tau via Lysosomal Exocytosis

Abstract: The pathological aggregation of tau characterizes a set of neurodegenerative diseases collectively referred to as tauopathies. Recent studies using cellular and animal models have suggested that tau pathology progresses by trans-cellular propagation. The process of propagation is mediated by certain species of extracellular tau, which are taken up by recipient cells and serve as a seed for tau aggregation. Tau propagation is currently one of the most active areas of research in dementia. Previous efforts to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…While highly sensitive and specific conformational antibodies would be ideal, amplification of tau seeds in purified systems [ 27 , 29 31 ] or in cultured “biosensor” cells has been the mainstay of sensitive and specific detection of pathological tau. Biosensor cells created by our group or others are now widely reported to detect pathological forms of tau [ 4 , 7 , 10 , 13 , 15 , 16 , 21 , 24 , 25 , 34 , 35 , 38 , 42 ]. Reliable measurement of tau seeding activity in a peripheral fluid such as CSF could be very useful in detection of incipient tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…While highly sensitive and specific conformational antibodies would be ideal, amplification of tau seeds in purified systems [ 27 , 29 31 ] or in cultured “biosensor” cells has been the mainstay of sensitive and specific detection of pathological tau. Biosensor cells created by our group or others are now widely reported to detect pathological forms of tau [ 4 , 7 , 10 , 13 , 15 , 16 , 21 , 24 , 25 , 34 , 35 , 38 , 42 ]. Reliable measurement of tau seeding activity in a peripheral fluid such as CSF could be very useful in detection of incipient tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that endolysosomes have to be rendered permeable for tau seeds in order to spread, interference in the formation of the late endocytic organelle arises as a potential intervention, by which RAB7, a well-known regulator of the fusion between endosomes and lysosomes, could be targeted [96,97]. RAB7 intervention would also affect unconventional tau secretion and autophagy [57,58,61]. Interestingly, formation of endolysosomes can also be blocked by interfering with PIKfyve (1-phosphatidylinositol 3-phosphate 5-kinase).…”
Section: Accepted Articlementioning
confidence: 99%
“…Recent studies have reported that lysosomal exocytosis is required for oligodendrocytes (OLGc) and Schwan cells myelination, suggesting that dysfunctional ELS could lead to white matter damage in HAND and AD ( Shen et al, 2016 ). Others have connected dysfunctional ELS with the dissemination and seeding of pTau, further implicating this system in tauopathies ( Tanaka et al, 2019 ; Jiang and Bhaskar, 2020 ; Polanco et al, 2021 ; Sebastián-Serrano et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%